Spiritual care as a response to an exaptation: how evolutionary psychology informs the debate - Kevern, Peter (Nursing philosophy, 2017)
This article has its origins in a 2013 proposal by the author that the concept of ‘spiritual care’ in clinical settings might fruitfully be grounded in the findings of the Cognitive Science of Religion (CSR). In a recent paper, John Paley rejects the central arguments and asserts his conviction that a model for ‘spiritual care’ cannot be derived from the insights of evolutionary psychology. In this article, the author employs a modified form of Fichtean dialectic to examine the contrasting positions and, via a process of analysis and synthesis, identify the key areas for further exploration and research. He concludes, first, that CSR in itself does not provide a sufficient theoretical justification for the notion and practice of ‘spiritual care’; secondly, that any attempt to develop a general theory of spiritual care would need to pay closer attention to the role of historically situated religious communities; and finally, that these objections nevertheless do not amount to an argument against the attempt to provide spiritual care as part of person-centred care. Instead, a revised model is proposed which has the potential to provide testable predictions in this field.